Education Equality and Economic Growth in Indonesia - Sabur, Ambuy; Khusaini, Khusaini; Ramdani, Heni Cahya (Universitas Negeri Semarang, 2021)
Last decade, Indonesia's economic growth experienced a downward trend. The study examines the role of investment, equality in education, poverty, income inequality, and regime to economic growth in Indonesia. We used time-series data between 1970-2017. It was obtained from BPS and World Bank (Indodapur) publications. The model used is the Weighted Least Square Regression (WLS). The results showed the factors that contributed significantly to increasing Indonesia's economic growth were education equality, poverty, and income inequality. While investment/capital, economic transparency, and the regime did not significantly contribute to increasing economic growth. Expanding access to education for high school or equivalent is important by the Government, including the development of school infrastructure in remote areas and teacher distribution. The Government should maintain the poverty trend that continues to decline. The future study dynamic models look at the long-term relationships related to education equality, distribution of income, and poverty on economic growth.